185k views
0 votes
5(5x+3) -4(2x-9)=0
pls help​

User Meiying
by
5.0k points

2 Answers

2 votes

Answer:

x = -3

Explanation:

5(5x+3) - 4(2x-9) = 0 Multiply out.

5*5x + 5*3 - 4*2x + 36 = 0

25x + 15 - 8x + 36 = 0 Combine like terms.

25x - 8x + 15 + 36 = 0

17x + 51 = 0 Subtract 51 from both sides.

17x = - 51 Divide each side by 17.

17x/17 = -51/17

x = - 3

User Yuby
by
5.2k points
3 votes

Answer:

x = -3

Explanation:

See steps of solution:

  • 5(5x+3) -4(2x-9)=0 ⇒ parenthesis
  • 25x + 15 - 8x + 36 = 0
  • (25x -8x) + (15 + 36) = 0 ⇒ grouping like terms
  • 17x +51 = 0
  • 17x = -51 ⇒ subtract 51 from both sides
  • x = -51/17 ⇒ divide both sides by 17
  • x = -3 ⇒ answer

Answer is -3

User Scott Mermelstein
by
5.4k points